2003
DOI: 10.1111/j.1464-410x.2004.04562.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute urinary retention secondary to benign prostatic hyperplasia in the UK: a national survey

Abstract: RESULTSWe received 270 (66%) replies, of which six were excluded because they were from subspeciality interests (e.g. paediatric urology) or had ambiguous answers; 264 (64%) were therefore available for analysis. Urethral catheterization was the initial management of choice (98%), failing which a suprapubic catheter was inserted. Two-thirds (65.5%) admitted the patient after catheterization. Most consultants initiated a -blockers (70.5%), with 64% (118) of these using a TWOC 2 days after starting them. One fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 30 publications
4
63
0
4
Order By: Relevance
“…In addition, Murray et al reported that up to 23% patients with AUR did not require prostatectomy based on urodynamic assessment [13]. In contrast, TWOC involves removing the catheter after 1-3 days, which allows 23%-40% of patients to void successfully [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Murray et al reported that up to 23% patients with AUR did not require prostatectomy based on urodynamic assessment [13]. In contrast, TWOC involves removing the catheter after 1-3 days, which allows 23%-40% of patients to void successfully [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Although a trial without catheter (TWOC) is the standard of care for AUR [5], TWOC typically involves removing the catheter after 3 days, which allows only 23%-40% of patients to void successfully [5,6]. TWOC in which catheter removal followed 2-3 days of -blocker (AB) improves success rates [7].…”
Section: Introductionmentioning
confidence: 99%
“…Основным лечебным мероприяти-ем, применяющимся для разрешения ОЗМ, является катетеризация мочевого пузыря (МП) -быстрый и эффективный способ эвакуации мочи. Согласно дан-ным, опубликованным в BJU, так поступают 98 % из опрошенных урологов Великобритании [9], причем длительность дренирования прямо пропорциональна вероятности восстановления самостоятельного моче-испускания и увеличивается в 1,4 раза при пролонгации этого периода с 1-х до 7-х суток [7]. Следует отметить, что обратной стороной длительной катетеризации яв-ляется риск присоединения уретральной инфекции и развития уретрита [10].…”
Section: Introductionunclassified
“…Так, 70,5 % из опрошен-ных урологов начинают терапию -адреноблокаторами непосредственно в день установки уретрального кате-тера [9].…”
Section: Introductionunclassified
“…Therefore, it seems to be important to characterize those patients who can be managed conservatively after AUR. Several studies propose a conservative approach with or without a period of α-blocking therapies [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%